Horrid Henry and the zombie vampire - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 2016)
Henry knows that a class sleepover at a museum can only be one thing--boring! So he's invited a few party crashers to liven things up...zombie vampires! Plus three other stories that will leave you screaming for more.
Horrid Henry writes a story -- Horrid Henry and the nudie foodie -- Horrid Henry and the mad professor -- Horrid Henry and the zombie vampire.
Ages 7-10.
English language and literature.
Keywords: Horrid Henry -- (Fictitious character) -- Juvenile fiction; Horrid Henry -- (Fictitious character) -- Fiction; Children's stories, English